2023
DOI: 10.3389/fpsyg.2023.1080099
|View full text |Cite
|
Sign up to set email alerts
|

Development of social anxiety cognition scale for college students: Basing on Hofmann’s model of social anxiety disorder

Abstract: IntroductionTo develop the Chinese version of the Social Anxiety Cognition Scale for College Students (SACS-CS) based on Hofmann’s model of social anxiety disorder and examine its reliability and validity.MethodsBased on literature analysis and structured interviews, a theoretical model was constructed and behavioral examples were collected. According to the results of participants’ and experts’ evaluations, the initial SACS-CS was developed. The study data were collected from a total of 500 valid participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Previous research has affirmed the significance of managing anxiety emotions among college students, as anxiety is a psychological factor that influences academic performance [3]. Instruments like the Social Anxiety Cognitive Scale for College Students (SACS-CS) have been developed, demonstrating good reliability and effectiveness [4]. Digital interventions are becoming increasingly popular for prevention and treatment [5].…”
Section: College Student Anxiety Emotionsmentioning
confidence: 99%
“…Previous research has affirmed the significance of managing anxiety emotions among college students, as anxiety is a psychological factor that influences academic performance [3]. Instruments like the Social Anxiety Cognitive Scale for College Students (SACS-CS) have been developed, demonstrating good reliability and effectiveness [4]. Digital interventions are becoming increasingly popular for prevention and treatment [5].…”
Section: College Student Anxiety Emotionsmentioning
confidence: 99%
“…Chao found that Chinese parents, who have a strong Confucian cultural impact, may have a propensity to embrace controlling parenting practices including psychological control [49]. According to Zha et al, social anxiety disorder is becoming more and more prevalent among Chinese college students, and their average degree of social anxiety is noticeably greater than average [50]. A prior survey found that 21.3 percent of Chinese college students used smartphones in inappropriate ways, and problematic smartphone use has become a public health problem in China [7].…”
Section: The Present Studymentioning
confidence: 99%